To determine which expressions produce the trinomial \(4x^2 - 20x - 24\), we can simplify each of the provided options and see if they yield the same expression.
-
Option 1: \(4(x - 6)(x + 1)\) \[ = 4(x^2 + x - 6x - 6) = 4(x^2 - 5x - 6) = 4x^2 - 20x - 24 \] This option works.
-
Option 2: \(-4(x^2 + 5x + 6)\) \[ = -4x^2 - 20x - 24 \] This option does not work. It yields an expression with a negative leading coefficient.
-
Option 3: \(4(x^2 - 5x - 6)\) \[ = 4x^2 - 20x - 24 \] This option works.
-
Option 4: \(4(x^2 - 20x - 24)\) \[ = 4x^2 - 80x - 96 \] This option does not work.
The two expressions that produce the trinomial \(4x^2 - 20x - 24\) are:
- \(4(x - 6)(x + 1)\)
- \(4(x^2 - 5x - 6)\)